Navigating a commercial literacy program: a first-year teacher's self-efficacy journey - Conway, Tracey Lynne (Kansas State University, 2024)
First-year teachers encounter many challenges throughout the beginning stages of their careers. One of those challenges relates to the navigation and implementation of district-mandated commercial literacy programs. When first-year teachers are expected to teach commercial literacy programs with fidelity, decisions about how to best implement the program to meet the needs of their specific group of students fall on their shoulders. Consequently, the level of a first-year teacher’s self-efficacy impacts their decision making in terms of the navigation and implementation of the program. With current calls to action for a shift in the focus of reading instruction across the country, this study holds significance, especially in terms of first-year teachers. The purpose of this study was to explore and understand in what ways, if any, does a first-year teacher’s level of self-efficacy impact the navigation and implementation of a commercial literacy program. This qualitative single case study design was grounded in the theoretical frameworks of Social Cognitive Theory and Self-Efficacy Theory, and employed Bandura’s proposed four sources of self-efficacy (mastery experiences, vicarious experiences, verbal persuasion, and physiological and affective states) as theoretical constructs to analyze the data from three different collection methods. Seven themes emerged from the data: Responsive Teaching Practices, Parents, Mentors, Literacy Curriculum, Professional Development, Planning, and Affective Domain. These seven themes aligned with one or more of Bandura’s four sources of self-efficacy. Verbal persuasion and mastery experiences were found to have the greatest amount of influence on the first-year teacher’s level of self-efficacy in terms of her use of the commercial literacy program.
Keywords: Self-efficacy; First-year teachers; Commercial literacy curriculum